Rv2617c and P36 are virulence factors of pathogenic mycobacteria involved in resistance to oxidative stress - Forrellad, Marina A. (2019)
Fil: Forrellad, Marina A. Instituto Nacional de Tecnología Agropecuaria (INTA). Instituto de Biotecnología. Hurlingham, Buenos Aires, Argentina.